Development of a Zero-Cement Binder Using Slag, Fly Ash, and Rice Husk Ash with Chemical Activator. (9th June 2015) - Karim, M. R.; Zain, M. F. M.; Jamil, M.; Lai, F. C.
Abstract : The increasing demand and consumption of cement have necessitated the use of slag, fly ash, rice husk ash (RHA), and so forth as a supplement of cement in concrete construction. The aim of the study is to develop a zero-cement binder (Z-Cem) using slag, fly ash, and RHA combined with chemical activator. NaOH, Ca(OH)2, and KOH were used in varying weights and molar concentrations. Z-Cem was tested for its consistency, setting time, flow, compressive strength, XRD, SEM, and FTIR. The consistency and setting time of the Z-Cem paste increase with increasing RHA content. The Z-Cem mortar requires more superplasticizer to maintain a constant flow of 110 ± 5 % compared with OPC. The compressive strength of the Z-Cem mortar is significantly influenced by the amounts, types, and molar concentration of the activators. The Z-Cem mortar achieves a compressive strength of 42–44 MPa at 28 days with 5% NaOH or at 2.5 molar concentrations. The FTIR results reveal that molecules in the Z-Cem mortar have a silica-hydrate (Si-H) bond with sodium or other inorganic metals (i.e., sodium/calcium-silica-hydrate-alumina gel). Therefore, Z-Cem could be developed using the aforementioned materials with the chemical activator.